Associations amongst genes, molecules, cells, and organs in breast cancer metastasis - Nathanson, David; Dieterich, Lothar; Zhang, Xiang H-F.; Chitale, Dhananjay A.; Pusztai, Lajos; Reynaud, Emma; Wu, Yi-Hsuan; Ríos-Hoyo, Alejandro (Clinical & experimental metastasis, 2023)
This paper is a cross fertilization of ideas about the importance of molecular aspects of breast cancer metastasis by basic scientists, a pathologist, and clinical oncologists at the Henry Ford Health symposium. We address four major topics: (i) the complex roles of lymphatic endothelial cells and the molecules that stimulate them to enhance lymph node and systemic metastasis and influence the anti-tumor immunity that might inhibit metastasis; (ii) the interaction of molecules and cells when breast cancer spreads to bone, and how bone metastases may themselves spread to internal viscera; (iii) how molecular expression and morphologic subtypes of breast cancer assist clinicians in determining which patients to treat with more or less aggressive therapies; (iv) how the outcomes of patients with oligometastases in breast cancer are different from those with multiple metastases and how that could justify the aggressive treatment of these patients with the hope of cure.
Vorab veröffentlicht: 09. September 2023
Gesehen am 18.10.2023